The Struggle of the Ukrainian Cossacks Against the Turkish-Tatar Expansion at the End of the 15th - the First Half of the 17th Century in the Works of Professor Mykola Kravets - Kravchuk, Oleksandr; Zinko, Yurii (Scientific Papers of the Vinnytsia Mykhailo Kotsyiubynskyi State Pedagogical University Series History, 2023)
The purpose of the article is to characterize the scientific works of Professor Mykola Kravets on the aggressive policy of the Sultanate of Turkey and the Crimean Khanate towards Ukrainian lands and the success of the Cossacks in defending the rights and freedoms of the Ukrainian people. The research methodology is based on the general scientific principles of objectivity, systematicity, historicism, combined with special historical methods: problematic-chronological, historical-biographical, descriptive, content analysis. The scientific novelty is an attempt to reveal the peculiarities of the military-political confrontation between the Ottoman Empire and the Crimean Khanate with the Ukrainian Cossacks and to present important pages of the successful struggle of the Cossacks against the Turkish-Tatar aggression in the late fifteenth century - the first quarter of the seventeenth century, based on the analysis of Mykola Kravets's works. Conclusions. In his works, Mykola Kravets examines the history of the Ukrainian Cossacks in the context of the military confrontation between the Cossacks and the Ottoman Empire and the Crimean Khanate and notes the role of the Cossack army in opposing the Turkish-Tatar expansion and protecting the rights of the Ukrainian people in the late fifteenth century - the first quarter of the seventeenth century. The author emphasizes the international significance of the Cossacks' struggle against Sultanist Turkey and the Crimean Khanate and points to their merits in protecting European peoples.